Psychoeducation on the Risks of Early Marriage to Reduce Early Marriage Intentions in Adolescents - Zainul Anwar; Maulida Rahmah (Psikologia : Jurnal Psikologi, 2016)
There are various reasons for someone to marry at an early age, one of which is the condition of someone who has a strong desire to marry at a young age. Early marriage intention is the tendency of a marriage that has a desire to marry at the age of teenagers or under the age of 20 years. The increasing intention of early marriage can be overcome, one of them is by providing psychoeducation. The purpose of this study was to determine the effect of providing psychoeducation on early marriage in reducing the intention of early marriage in adolescents. The research subjects were 55 teenagers who were taken purposively. This research is a quasi-experimental research. This type of research uses a pre-experimental design method with the type of pre-test and post-test one group design. The results showed that there was a significant difference in scores for the treatment without psychoeducation and with the treatment with psychoeducation t (-39.305; p = 0.000 <0.05). Thus, it can be concluded that psychoeducation can be used to reduce early marriage intentions.